1991
DOI: 10.1677/jme.0.0060179
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone induces expression of c-jun and jun B oncogenes and employs a protein kinase C signal transduction pathway for the induction of c-fos oncogene expression

Abstract: Although the structure of several members of the GH receptor family has been defined, signal transduction following GH binding to its receptor has not been elucidated. Mouse osteoblasts were used to study the effect of GH on immediate early gene expression and, subsequently, the cellular signal(s) mediating this expression were analysed. GH rapidly and transiently induced the expression of c-jun and jun B in concert with the already reported expression of c-fos. The GH-induced expression of c-fos was completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 47 publications
2
20
0
1
Order By: Relevance
“…Stimulation of c-f os mRNA by hGH was also noticeably attenuated in cells treated with protein kinase inhibitors, staurosporine and H-7, whereas genistein, a tyrosine kinase inhibitor was without effect. The result is consistent with the previous report that c f os mRNA expression by GH was inhibited by H-7 or staurosporine [3], so that it appears that c-f os mRNA expression by GH is largely mediated by PKC. Preliminary experiments have shown that hGH increases a transient and small increase in PKC activity in the membranes of 3T3 L-1 cells.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Stimulation of c-f os mRNA by hGH was also noticeably attenuated in cells treated with protein kinase inhibitors, staurosporine and H-7, whereas genistein, a tyrosine kinase inhibitor was without effect. The result is consistent with the previous report that c f os mRNA expression by GH was inhibited by H-7 or staurosporine [3], so that it appears that c-f os mRNA expression by GH is largely mediated by PKC. Preliminary experiments have shown that hGH increases a transient and small increase in PKC activity in the membranes of 3T3 L-1 cells.…”
Section: Resultssupporting
confidence: 93%
“…As reported for 0B1771 cells [2] and mouse osteoblasts [3], hGH stimulated a transient expression of c f os mRNA and c jun within 20 min, and their expression became undetectable within 2 h after GH stimulation.…”
Section: Resultssupporting
confidence: 76%
“…The c-fos C/EBP site, which binds the transcription factors C/EBPβ and C/EBPδ, is also regulated by GH (16). Further, since the c-fos enhancer also contains an AP-1 site, it is of interest that GH also induces binding of Fos and Jun family proteins to this element (41)(42)(43). Deletion analysis of the c-fos promoter suggests that each of these transcription factor binding sites contributes to GH-regulated c-fos promoter activation (44).…”
Section: Gh Regulates Transcription By Modifying the Activity Of Multmentioning
confidence: 99%
“…The GH receptor is a member of the cytokine/hematopoietin family and shares structural motifs with other members of this family (21). Hormone binding induces GH receptor dimerization (6,16), and the dimerized receptor binds to and activates JAK2 (1,32), an intracellular tyrosine protein kinase that can also interact with receptors for gamma interferon (42,43,55), erythropoietin (56), prolactin (12,34), and other members of the cytokine/hematopoietin receptor family (45,47). Previous studies on the gamma interferon signal transduction pathway have identified a cytoplasmic protein, termed Stat1 (formerly Stat91, for signal transducer and activator of transcription), that undergoes tyrosine phosphorylation and nuclear translocation in response to receptor activation (8,40).…”
mentioning
confidence: 99%
“…GH acutely stimulates the transcription of several target genes, including c-fos (11,20,24,47) and the IGF-I (2) and serine protease inhibitor (Spi) 2.1 (59,60) genes, but the ciselements and trans-acting factors involved in GH-activated gene expression remain undefined. Transcription of the earlyresponse gene, c-fos, is induced by a variety of cellular growth factors through cis-acting elements in the c-fos 5Ј flanking region, such as the serum response element (53) and SIE (c-sis-inducible element).…”
mentioning
confidence: 99%